Improving the hydro-morpho dynamics of a river confluence by using vanes - Ali, Hydar Lafta; Yusuf, Badronnisa; Mohammed, Thamer Ahmed; Shimizu, Yasuyuki; Ab Razak, Mohd Shahrizal; Mohamed Rehan, Balqis (MDPI, 2019)
Controlling the flow and bed morphology in a river confluence is important in training and navigation works. The flow in river confluence is highly complex due to crucial and rapid changes associated with flow dynamics, sediment transport, and geomorphology. The flow in Malaysia’s rivers has many confluence junctions in natural drains of catchment areas. The confluence between Kurau and Ara Rivers, in Perak, Malaysia, is selected to investigate the scour hole that usually forms in the erosion zone and the bar that forms in the deposition zone. A 2D numerical model is used in simulating hydro-morpho dynamics in the rivers confluence to mitigate the erosion and deposition zones by adopting vanes as control structures. Simulation results suggest that the most effective location, dimension, and angle of vanes can be decided based on their performance in scouring and deposition zones. The distribution velocity and flow vectors can help in deciding the location of the vanes.